2004
DOI: 10.1540/jsmr.40.249
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine-induced vasoconstriction of the rat superior mesenteric artery is decreased after repeated swimming

Abstract: This study was performed to determine the effect of forced swimming on the vascular responsiveness of the rat superior mesenteric artery to phenylephrine, focusing on the involvement of locally produced substances. Repeated but not single sessions of forced swimming exercise reduced the vasoconstrictor potency of phenylephrine in the studied arteries, regardless of the presence of intact endothelium. No significant changes were observed in the maximal response to phenylephrine. Treatment with indomethacin (1 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Our study clearly showed that the vasoconstrictive responses to α 1 -adrenoceptor stimulation in the aorta and the caudal, pulmonary and mesenteric arteries from the exhaustively exercised rats were significantly smaller than those from the normal rats, and a rank order of the decrease in the maximal vasoconstriction was determined as follows: mesenteric artery, pulmonary artery, caudal artery, aorta. Similar results were reported in the endothelium-denuded aorta [32] and mesenteric artery [33] from normal rats subjected to physical exercise. Moreover, we found that the P2X 1 receptor-mediated vasoconstriction in all 5 arterial subtypes was not affected by exhaustive exercise.…”
Section: Wwwnaturecom/aps LI L Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study clearly showed that the vasoconstrictive responses to α 1 -adrenoceptor stimulation in the aorta and the caudal, pulmonary and mesenteric arteries from the exhaustively exercised rats were significantly smaller than those from the normal rats, and a rank order of the decrease in the maximal vasoconstriction was determined as follows: mesenteric artery, pulmonary artery, caudal artery, aorta. Similar results were reported in the endothelium-denuded aorta [32] and mesenteric artery [33] from normal rats subjected to physical exercise. Moreover, we found that the P2X 1 receptor-mediated vasoconstriction in all 5 arterial subtypes was not affected by exhaustive exercise.…”
Section: Wwwnaturecom/aps LI L Et Alsupporting
confidence: 89%
“…Moreover, exercise training increases acetylcholine-induced relaxation and eNOS protein levels in the porcine pulmonary artery [29,30] , but not in the pulmonary artery from hypertensive rats [31] . Therefore, we removed the vascular endothelium of the isolated mesenteric, pulmonary, caudal and internal carotid arteries from the rat to directly observe the changes in α 1 -adrenoceptor-and P2X 1 receptor-mediated vascular smooth muscle contractions because several studies suggest that exercise affects not only the vasoconstriction of vascular smooth muscles [32,33] , but also the function of the vascular endothelium [26,27] . NA induces vasoconstriction and vasodilatation via α-adrenoceptors and β-adrenoceptors.…”
Section: Wwwnaturecom/aps LI L Et Almentioning
confidence: 99%
“…The swimming protocol was adapted from Chies et al (19). We used a rectangular polyethylene tank measuring 120 cm in length, 50 cm in deep and 43 cm wide with water at a temperature of 29 ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%
“…On the few occasions that the elastic ribbon slipped off the rat's chest, the researcher paused the timer, adjusting the ribbon and continued the exercise test. The metal rings in groups G3, G4, G5, G6 and G8 represented 3, 4, 5, 6 and 8% of the animal's body weight, respectively, corresponding to the exercise intensity range they were subjected to (19). Gobatto et al (16) identified that in the rats the maximal lactate steady state level (MLSS) is achieved with exercise loads of 5 to 6%.…”
Section: Methodsmentioning
confidence: 99%
“…Most, but not all (134, 186), in vitro studies examining the splanchnic and renal vasculature have revealed enhanced ACh-induced vasodilation and reduced vasoconstriction to various agonists (nor-epinephrine, phenylephrine, prostaglandin F2α, KCl) related, at least in part, to enhanced production of and/or sensitivity to endogenous endothelial dilators (i.e., nitric oxide, prostacyclin, etc.) (4, 19, 20, 25, 42, 43, 74, 92, 112, 214). Mechanistically, the training-induced enhancement of mesenteric vasodilation to ACh appears to be accounted for by an enhanced endothelium-derived hyperpolarizing factor-dependent component of ACh dilation and subsequent activation of calcium activated K + channels (19, 214); however, other unexamined pathways may be involved as well.…”
Section: Effects Of Exercise Training On the Endothelium Of Noncontramentioning
confidence: 99%